Trends of fall-related and other fatal injuries in older adults in Finland between 1998 and 2020 - Ylitörmänen Tuija; Nuotio Maria S.; Kettunen Hanna; Impinen Antti; Koivula Riitta; Haikonen Kari (Oxford University Press, 2025)
Background
The number of falls and fall-related injuries will likely increase as the number of older adults expands. Increases in total deaths due to falls have been observed over Europe. Less is known about other injuries leading to death.
To examine the incidence trends of fall-related and other fatal injuries among adults aged 65 or older in Finland.
Methods
We analyzed open data from Statistics Finland’s register on the causes of death of those aged ≥65 collected between 1998 and 2020 yielding a total of 32 150 deaths due to injury using Poisson regression and distributional comparisons chi-squared tests.
Results
The most common injuries leading to death among people aged ≥65 in Finland were fall related. There has been an increase in the absolute number of fall-related and other injuries, but when adjusting for person-years in population, a significant decrease can be observed. The crude rates of deaths from fall-related injuries among males annually increased 1.1–4.4% from 1998 to 2020, while the changes in rates among females ranged between −2% and 1.6%. The crude rates of other injuries ranged between −0.5% to +3.8%. Recently (2018–20), nearly 40% of the cases in males and 25% of cases in females were not fall related but comprised other types of injury mechanisms such as traffic, poisoning and drowning.
Conclusion
Strengthening the implementation of preventive strategies is essential to prevent injuries. To reduce injury-related mortality and disability, improvement of acute and post-acute care for injured older patients is warranted.